The delivery of specialist spinal cord injury services in Queensland and the potential for telehealth. Issue 1 (December 2015) - van de Pol, Eileen; Lucas, Karen; Geraghty, Timothy; Pershouse, Kiley; Harding, Sandra; Atresh, Sridhar; Wagemakers, Annemarie; Smith, Anthony
Abstract Background The Queensland Spinal Cord Injuries Service (QSCIS) is a statewide service in Brisbane at the Princess Alexandra Hospital (PAH). The QSCIS assists individuals with a spinal cord injury (SCI) through three services: the Spinal Injuries Unit (SIU), Transitional Rehabilitation Program (TRP) and the Spinal Outreach Team (SPOT). The aim of this study was to undertake a review of ambulatory services provided by the QSCIS (SIU and SPOT) to help identify where telehealth may potentially be useful. Methods Profiling of patients with SCI in Queensland was achieved using database records containing referral data. Services provided by SIU Outpatient Clinics and the SPOT during a 6-year period (January 2008 – December 2013), were analysed. Using postcodes, we estimated distances between place of residence and Brisbane. We compared the general population of SCI patients with patients managed through SIU Outpatient Clinics and the SPOT. Results During the 6-year period, 2073 patients were referred to the QSCIS (and living) at the time of the analysis. 74 % of all patients were male. The median age was 51y (IQR 39y-61y). About two-thirds of all patients lived within 200 km of Brisbane. 24 % of all patients registered with the QSCIS lived further than 200 km away from Brisbane. 7513 appointments were provided in the SIU outpatient clinic. 43, 827 occasions of service were reported by the SPOT, including telephone consultations (66 %) and home visits (26 %). 72 outreach clinics were held in selected regional sites for up to 100 patients per year. 13 videoconference appointments reported. 90 % of all patients who attended the SIU outpatient clinic lived within 200 km of Brisbane. About two-thirds of patients who received a service from the SPOT lived within 200 km of Brisbane. Conclusion Since one third of all patients registered with the QSCIS live at least 200 km away from Brisbane; it appears that these patients may not be accessing the same services as Brisbane based patients. Telehealth models of care, which promote better engagement with local health service providers (such as general practitioners, nurse practitioners and allied health professionals) could improve equity of access and reduce the need for extensive travel.